(untitled) (Journal of Medicine, 2021)
Background: In general, reinfection means a person was infected (got sick) once, recovered, and then later became infected again. Based on what we know from similar viruses, some reinfections are expected. We are still learning more about COVID-19. Ongoing COVID-19 studies will help us to understand.The degree of protective immunity conferred by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is currently unknown. As such, the possibility of reinfection with SARS-CoV-2 is not well understood. Here we describe presentation and investigations of two instances of SARS-CoV-2 infection in the same individual. Methodology : A 38-year-old man who is a resident of Dhaka city , Engineer by profession presented to doctors on two occasions with symptoms of viral infection. First time at a community testing event in June, 2020, and a second time to Evercare hospital at the mid November , 2020. Nasopharyngeal swabs were obtained from the patient at each presentation and twice during follow-up. RT PCR testing was done to confirm SARS-CoV-2 infection. CXR P/A view was performed in 1st time of Covid infection & HRCT of chest was performed during his stay at Evercare hospitals Findings: The patient had two positive tests for SARS-CoV-2, the first on June 20th, 2020, and the second on November 18th 2020, separated by two negative tests done during follow-up in July, 2020. The second infection was symptomatically more severe than the first with remarkable radiological changes of Chest in high resolution CT scanning . Interpretation: Two subsequent negative RT PCR after 1st positive with clinically asymptomatic period after 2 weeks of mild symptoms was observed in our patient . About 5 months later he was Covid19 positive again with moderate symptoms. These findings suggest that the patient was infected by SARS-CoV- 2 on two separate occasions probably by genetically distinct virus. Thus, previous exposure to SARS-CoV- 2 might not guarantee total immunity in all cases. All individuals, whether previously diagnosed with COVID- 19 or not, should take identical precautions to avoid infection with SARS-CoV-2. The implications of reinfections could be relevant for vaccine development and application. J MEDICINE JAN 2021; 22 (1) : 77-80